Rapid improvement in symptoms and physical function following ibrutinib initiation in chronic lymphocytic leukemia and the associated changes in plasma cytokines. (October 2021) - Ishdorj, G.; Nugent, Z.; Squires, M.; Kost, S.; Banerji, V.; Davidson, L.; Katyal, C.S.; Marshall, A.; Gibson, S.B.; Johnston, J.B.
Highlights: Significant improvement in fatigue, shortness of breath and a sense of unwellness occurs within 2 weeks of starting ibrutinib in CLL patients. Ibrutinib rapidly improves physical activities, such as sit-to-stand and 4 m walking speeds, in CLL patients. Ibrutinib suppresses the inflammatory cytokine and signaling molecules, TNF-α/-β, CCL3, CCL4, CCL17, and IL-16 levels, in CLL patients. Abstract: A prospective pilot study was carried out on 34 CLL patients treated with ibrutinib, evaluating the effects on symptoms and physical function with changes in plasma exosomes (EXs), β2-microglobulin (β2M) and 26 plasma cytokines. The revised Edmonton Symptom Assessment Scale (ESAS-R) demonstrated moderate fatigue, shortness of breath and a sense of unwellness before treatment, which significantly improved within 2 weeks of starting ibrutinib. These changes were associated with a rapid improvement in sit-to-stand and 4 m walking speeds. The plasma levels of CCL11, IL-7, -8 and -10 dropped initially while the levels of TNF-α/-β, CCL3, CCL4, CCL17, and IL-16 continued to decline for 12 months. Despite the initial lymphocytosis, plasma β2M levels fell but no consistent change in plasma EXs occurred. Thus, ibrutinib can produce a rapid and sustained improvement in symptoms and physical function in CLL, associated with a decline in multiple plasma cytokines.